Prevalence of Moral Decadence Among Youths in Kaduna North Local Government Area, Kaduna State - Lukman, Jamila (NIU Journal of Humanities; Vol 6 No 1 (2021): KIU Journal of Humanities, Vol. 6 No. 1, March 2021, 2021)
This study is on the prevalence of moral decadence in Kaduna North Local Government Area of Kaduna State. Moral decadence has been an issue in the Nigerian society today, especially in urban areas. Kaduna North Local Government Area is one of those urban areas that have witnessed a rise in moral decadence committed mostly by youths. These immoral acts range from examination malpractices, indecent dressing, drug abuse, among others. The study adopted the Social Learning Theory, as it explains that individuals, especially youths, tend to learn and act based on their observation in the society. The research made use of primary and secondary types of data. Questionnaires were distributed in the study area. Books, Journals, Newspapers as well as online materials were also used. The findings of this study revealed that parents have neglected their roles with regards to moral teachings. Similarly, poverty and unemployment, peer influence and technology have also played a huge role in the collapse of morality in the study area. The study therefore suggested that there is the need for parents to firmly educate their children about moral norms and values. The government will also do well to create job opportunities, especially among youths. There is also the need to include religious leaders in the fight against moral decadence in the society. Keywords: Youth, Moral Decadence, Immorality, Kaduna.